Understanding maternal choices and experiences of care by skilled providers: Voices of mothers who delivered at home in selected communities of Lusaka city, Zambia - Jacobs, Choolwe; Michelo, Charles; Hyder, Adnan (Frontiers in Global Women's Health, 2023)
Background Significant proportions of women living in urban areas including the capital cities continue to deliver at home. We aimed to understand why mothers in a selected densely populated community of Lusaka city of Zambia deliver from home without assistance from a skilled provider during childbirth. Methods Using a phenomenological case study design, we conducted Focus Group Discussions and In-depth Interviews with mothers who delivered at home without assistance from a skilled provider. The study was conducted between November 2020 and January 2021 among 19 participants. Data was analysed using content analysis. Results Individual related factors including; the belief that child birth is a natural and easy process that did not require assistance, lack of transport to get to the health facility, Influence and preference for care from older women who were perceived to have the experience and better care, failure to afford baby supplies and waiting for partner to provide the supplies that were required at the health facility influenced mothers’ choices to seek care from skilled providers. Health System Related factors included; Mistreatment and disrespectful care such as verbal and physical abuse by skilled health care providers, stigma and discrimination, institutional fines and guidelines such as need to attend ANC with a spouse and need to provide health facility demanded supplies. Conclusion Individual and health system access related factors largely drive the choice to involve skilled providers during child birth. The socio-economic position particularly contributes to limited decision-making autonomy of mothers thus creating challenges to accessing care in health facilities. While the health system related factors found in this study such as mistreatment and disrespectful care suggests need for re-designing effective and sustainable urban resource-limited context maternal health strategies that are culturally-acceptable, non-discriminatory and locally responsive and inclusive. Re-thinking these strategies this way has the potential to strengthening equitable responsive health systems that could accelerate attainment of SDG 3 targets.